The use of active learning in a private higher education institution: The lecturer's perspective - Beyleveld, M.; de Villiers, J.J.R.; Fraser, W.J. (South African Journal of Higher Education, 2019)
Lecturers could potentially have different reasons why they would choose a specific teaching strategy including government policy, education institution policy or management directive. Despite these factors lecturers could also choose to use Active learning strategies out of their own accord and not because they are being told so. This qualitative interpretive case study sets out to understand the views of 11 lecturers teaching in three different faculties: Faculty of Commerce and Law, Faculty of Social Science and Faculty of Applied Science, in a private higher education institute in South Africa on their motivation in using Active learning strategies in their classrooms. The findings suggest that lecturers are using Active learning due to them believing that: Active learning prepares students for the workplace by developing the required skills; supports learning in the classroom; changes boring passive learning classes into to engaging enjoyable active classes in which students want to participate; and their own experience as a student having had a lecturer that used Active learning strategies in their classes that worked for them.